Effects of modified lifestyle intervention education on arterial stiffness, inflammatory and metabolic risk markers in overweight and obese subjects - Ariffin, Farah Diana (2013)
Obesity is a global epidemic disease affecting almost all parts of the world. The prevalence of obesity has increased rapidly in the last ten years in Malaysia. Obesity increases the risk of medical problems and cardiovascular diseases. Lifestyle modification by improving dietary intake combined with increasing physical activity is the recommended method for the improvement in body composition.